Fotoetnografia da xondaro jeroky: a dança do xondaro da cultura guarani - Castro, Carlos Eduardo de (2023)
In the present work we aim to produce a Photoethnography about the xondaro jeroky, the xondaro dance, which represents the training of the Guarani warrior, to prove the effectiveness and efficiency of Photoethnography as a methodology in the field of Visual Anthropology, to register this manifestation of the Guarani culture , as well as presenting and describing the elements of photographic language that can be conducive to the production of a photoethnographic work. We carried out our fieldwork at Núcleo Cachoeira da Terra Indígena Ribeirão Silveira, located between the municipalities of Bertioga and São Sebastião, on the coast of São Paulo, producing a part of the images that make up this Photoethnography between 2021 and 2022, while the other part of the images is composed of images of our activity in the area of documentary photography in the village, carried out between 2013 and 2021. We divide this work into two distinct parts, which, we suggest to the reader, be appreciated separately, namely: the scientific text and the photoethnographic narrative. Photoethnography is a methodology conceived in the 1990s by the photographer and anthropologist Luiz Eduardo Robinson Achutti, who is the main theoretical reference of this work. This methodology consists of building photographic narratives at the service of the anthropological gaze, as we understand that visual narratives carry great communicational potential, which is optimized when well combined with the text, each in its proper space. We believe that this dissertation has an innovative character because it is the first Photoethnography carried out with an indigenous population. Therefore, we understand that the originality of the theme, as well as the breadth of fieldwork and the consequent uniqueness of some types of images, brings unique value to this Photoethnography.